2015
DOI: 10.1590/1516-635xspecialissuenutrition-poultryfeedingadditives015-022
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme Supplementation of Broiler Feeds with Reduced Mineral and Energy Levels

Abstract: An experiment was conducted with the purpose of evaluating enzyme blends on the performance, carcass traits, and bone mineralization of broilers. In total, 928 one-day-old Cobb 500 male chicks of were used. A completely randomized design with four treatments with eight replicates of 29 birds each was adopted. The evaluated treatments were: 1-Positive Control (PC), feed containing the nutritional recommendations of the genetic company's manual; 2-Negative Control (NC), feed with reductions of 75 kcal/kg AME and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
3
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 18 publications
4
3
0
2
Order By: Relevance
“…As previously discussed by Nunes et al (2015), the use of enzyme supplementation improved the performance of broilers by reducing the amount of nutrients and energy required. Moftakharzadeh et al (2019) indicated that the use of enzymatic supplementation increased energy utilization from wheat and soybean based diets.…”
Section: Introductionmentioning
confidence: 74%
“…As previously discussed by Nunes et al (2015), the use of enzyme supplementation improved the performance of broilers by reducing the amount of nutrients and energy required. Moftakharzadeh et al (2019) indicated that the use of enzymatic supplementation increased energy utilization from wheat and soybean based diets.…”
Section: Introductionmentioning
confidence: 74%
“…Higher feed intake, higher body weight gain and better feed conversion ratios were found in the quails for the PC diet, compared to the NC diet, with and without protease supplementation. According to Nunes et al (2015) the nutrient and energy reductions of the NC treatment effectively allow for the statistical performance differentiation from the PC diet. In the present study, it was also observed that the reduction of crude protein and amino acids in the NC diets, compared to the PC diets, allowed effective differentiation of the variation in the performance of the quails.…”
Section: Parametersmentioning
confidence: 99%
“…The protease under analysis did not improve digestion and further absorption of protein, since it was not specific for the degradation of keratin; consequently, quails fed on diets including protease did not have the highest body weight gain. Nunes et al (2015) reported that, among other reasons, the enzyme supplementation may not have been efficient enough to allow for similar performance as that obtained with the standard diet (PC), due to the higher lipid (oil) level of the diet, which has less impact on the heat increment compared with carbohydrates and proteins. These results are in agreement with those of our study.…”
Section: Parametersmentioning
confidence: 99%
“…xilanase, glucanase, celulase, mananase e pectinase foram avaliadas em dietas de frangos de corte de linhagem industrial que contêm níveis elevados de polissacarídeos não Brazilian Journal of Development, Curitiba, v.7, n.8, p. 84829-84847 aug. 2021 amiláceos (PNA's) e verificaram melhoria na metabolizabilidade dos nutrientes e no desempenho das aves (ABDOLLAHI et al, 2016;BARBOSA et al, 2012;NUNES et al, 2015).…”
Section: Introductionunclassified